DIGITAL TECHNOLOGY Investigating consultant-led virtual review as a model for implementing 7-day cardiology services in UK clinical practice. Issue 3 (2021) - Deighton, Alexander J; Davies, Ceri; Bourantas, Christos; Knight, Charles; Woldman, Simon; Azar, James Deighton Armita; Das, Debashish
No abstract available